The Characterizations of Professor Snape in J. K. Rowling’s Harry Potter And The Philosopher’s Stone - Suwastini, Ni Komang Arie; Wahyuni, Luh Gede Eka; Agustina, Luh Winda; Hartanto, Erika Citra Sari; Artini, Ni Nyoman (International Journal of Language and Literature, 2022)
J. K. Rowling’s Harry Potter and the Philosopher's Stone has presented readers with different unique teachers. Even though Rowling’s series disclose Professor Snape as a hero, the first novel depicted him as an insufferable character set to thwart the main characters’ adventure. This study aimed to provide more objective portrayals of Professor Snape through interactive qualitative data analysis. The subject of the study is J. K. Rowling’s Harry Potter and the Philosopher’s Stone. Meanwhile, the characterizations of Professor Snape become the object of the study. As the main instrument of data collection, the researcher conducted close reading. The analysis consisted of a concurrent process of data condensation, data display, and conclusion drawing, which are also synchronized with the data collected at the beginning of the research. This study reveals that Professor Snape was depicted as knowledgeable, curious, observant, hardworking, loner, partial, loyal, responsible, and authoritative. These results show that Professor Snape has good characters. However, they were overshadowed by his brooding appearance. This conclusion implies that students should not judge their teacher or others based on their appearance.